Patronage, politics and performance: radio call-in programmes and the myth of accountability. - Stremlau, Nicole; Fantini, Emanuele; Gagliardone, Iginio (Third World Quarterly, 2015)
The role of media in promoting political accountability and citizen participation is a central issue in governance debates. Drawing on research into the interactions between radio station owners, journalists, audiences and public authorities during Somali radio call-in programmes we argue that these programmes do not simply offer a new platform for citizens to challenge those who are governing but that they are also spaces where existing power structures reproduce themselves in new forms. We identify the ways the programmes are structured and the different motivations the audience has for participation. Three types of programmes are identified and their relationships with patronage, politics, and performance are examined. Rather than focusing on normative assumptions about the media as a tool of accountability, the article emphasises the importance of understanding radio programmes in their social and political environment, including the overlapping relationships between on-air and off-air networks.